Dataset of the vascular e-Learning during the COVID-19 pandemic (EL-COVID) survey - Nikolaos Patelis; Theodosios Bisdas; Zaiping Jing; Jiaxuan Feng; Matthias Trenner; Nyityasmono Tri Nugroho; Paulo Eduardo Ocke Reis; Stephane Elkouri; Alexandre Lecis; Lamisse Karam; Dirk Le Roux; Mihai Ionac; et al. (Data in Brief, 2021)
This dataset supports the findings of the vascular e-Learning during the COVID-19 pandemic survey (the EL-COVID survey). The General Data Protection Regulation (GDPR) of the European Union was taken into consideration in all steps of data handling. The survey was approved by the institutional ethics committee of the Primary Investigator and an online English survey consisting of 18 questions was developed ad-hoc. A bilingual English-Mandarin version of the questionnaire was developed according to the instructions of the Chinese Medical Association in order to be used in mainland People's Republic of China. Differences between the two questionnaires were minor and did affect the process of data collection. Both questionnaires were hosted online.The EL-COVID survey was advertised through major social media. All national and regional contributors contacted their respective colleagues through direct messaging on social media or by email. Eight national societies or groups supported the dissemination of the EL-COVID survey.The data provided demographics information of the EL-COVID participants and an insight on the level of difficulty in accessing or citing previously attended online activities and whether participants were keen on citing these activities in their Curricula Vitae. A categorization of additional comments made by the participants are also based on the data.The survey responses were filtered, anonymized and submitted to descriptive analysis of percentage.